Role of CD8 in aberrant function of cytotoxic T lymphocytes. - Kessler, B; Hudrisier, D; Cerottini, J; Luescher, I (1997)
Using H-2Kd-restricted photoprobe-specific cytotoxic T lymphocyte (CTL) clones, which permit assessment of T cell receptor (TCR)-ligand interactions by TCR photoaffinity labeling, we observed that the efficiency of antigen recognition by CTL was critically dependent on the half-life of TCR-ligand complexes. We show here that antigen recognition by CTL is essentially determined by the frequency of serial TCR engagement, except for very rapid dissociations, which resulted in aberrant TCR signaling and antagonism. Thus agonists that were efficiently recognized exhibited rapid TCR-ligand complex dissociation, and hence a high frequency of serial TCR engagement, whereas the opposite was true for weak agonists. Surprisingly, these differences were largely accounted for by the coreceptor CD8. While it was known that CD8 substantially decreases TCR-ligand complex dissociation, we observed in this study that this effect varied considerably among ligand variants, indicating that epitope modifications can alter the CD8 contribution to TCR-ligand binding, and hence the efficiency of antigen recognition by CTL.